Evaluation of chemical risks by inhalation of substances used in a graphic industry - Villalobos-González, Wendy (2021)
In the production process of a graphic industry, inputs and raw materials used for printing documents. An input are chemical products that could generate a chemical risk, if not properly controlled through protocols for use, storage and disposal of waste. Some chemical substances used: inks, solvents, thinners, glues, protective rubbers, plate developers, among others. Chemical inhalation risk (RQI) generated in the workplace using substances with amounts of volatile organic compounds (VOCs), which could adversely affect the health of workers. A chemical risk assessment involves evaluating factors such as: the amount of a chemical, the exposure of a person with the contaminant in the environment and the toxicity of the chemical; its purpose is to identify and evaluate chemical substances and generate measures to reduce the impact on health. In the present research project an identification, valorization and prioritization of the level of chemical risk by inhalation (NRQI) generated in a lithographic offset industry in Costa Rica carried out. The identification of risks and dangers carried out using tools such as: literature review, checklist, interviews and field inspections. The valuation and prioritization of the RQI carried out using the French methodology of the National Institute for Security Research (INRS). Of the 15 chemical products used by the industry, it obtained that 53.3 % have a very high RQI. The products with the highest NRQI value were the thinner and the roller cleaner, which used for cleaning machines, with a frequency of continuous use in quantities between 0,7 L/month and 20,0 L/month. On the contrary, five products with low NRQI values identified, such as: ink in cartridge, coolant, cleaner 4, isopropanol and plate gum.